Wobble Editing of Cre-box by Unspecific CRISPR/Cas9 Causes CCR Release and Phenotypic Changes in Bacillus pumilus - Wang, Yingxiang; Cao, Linfeng; Bi, Meiying; Wang, Sicheng; Chen, Meiting; Chen, Xingyu; Ying, Ming; Huang, Lei (Frontiers in Chemistry, 2021)
CRISPR-associated Cas9 endonuclease (CRISPR/Cas9) systems are widely used to introduce precise mutations, such as knocking in/out at targeted genomic sites. Herein, we successfully disrupted the transcription of multiple genes in Bacillus pumilus LG3145 using a series of unspecific guide RNAs (gRNAs) and UgRNA:Cas9 system-assisted cre-box editing. The bases used as gRNAs shared 3070% similarity with a consensus sequence, a cis-acting element (cre-box) mediating carbon catabolite repression (CCR) of many genes in Bacillus. This triggers trans-crRNA:Cas9 complex wobble cleavage up/downstream of cre sites in the promoters of multiple genes (up to 7), as confirmed by Sanger sequencing and next-generation sequencing (NGS). LG3145 displayed an obvious CCR release phenotype, including numerous secondary metabolites released into the culture broth, pigment overflow causing a colour change, polysaccharide capsules appearing outside cells, and improved sugar tolerance. We assessed the relationship between carbon catabolite pathways and phenotype changes caused by unspecific UgRNA-directed cre site wobble editing. We propose a novel strategy for editing consensus targets at operator sequences that mediates transcriptional regulation in bacteria.